2021
DOI: 10.1186/s40246-021-00316-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and validation of related hub gene expression during SARS-CoV-2 infection of human bronchial organoids

Abstract: Background In the novel coronavirus pandemic, the high infection rate and high mortality have seriously affected people’s health and social order. To better explore the infection mechanism and treatment, the three-dimensional structure of human bronchus has been employed in a better in-depth study on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods We downloaded a separate microarray from the Integrated Gene Expression System (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Importantly, downregulation of the RTCA‐AS1 in SARS‐CoV‐2‐infected human bronchial organoids has been reported. 9 Additionally, we found that SOB patients were closer to the mild, while the RS were similar to moderate for their lncRNA expression (Figure 3E ).…”
mentioning
confidence: 74%
“…Importantly, downregulation of the RTCA‐AS1 in SARS‐CoV‐2‐infected human bronchial organoids has been reported. 9 Additionally, we found that SOB patients were closer to the mild, while the RS were similar to moderate for their lncRNA expression (Figure 3E ).…”
mentioning
confidence: 74%
“…Several lines of evidence support the role of HLA-G in COVID-19 pathogenesis, including (i) the increased levels of sHLA-G molecules in patients exhibiting various clinical manifestations of the disease [ 14 , 15 , 16 , 17 , 18 ], (ii) the increased number of immune system cells expressing HLA-G [ 16 , 19 ], (iii) the association of the HLA-G 3′untranslated region polymorphism with susceptibility to the disease [ 18 ], (iv) the increased tissue expression of HLA-G in case reports [ 20 , 21 ], and (v) the induction of the expression of hub genes, including HLA-G , in lung tissue infected by SARS-CoV-2 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The top five commonly enriched MFs (ubiquitin binding, sequence-specific DNA binding, CCR chemokine receptor binding, chemokine activity) by cHubGs, are significantly associated with both COVID-19 and IPF disease 59,75,76 . Similarly, the association of top four CCs (tertiary granule lumen, early endosome, extracellular space, cytosol, extracellular region) with COVID-19 and IPF disease were supported by the literature review 66,[77][78][79][80][81][82][83] . The top five commonly enriched KEGG pathways (TNF signaling, IL-17 signaling, NF-kappa B signaling, NOD-like receptor signaling and Cytokine-cytokine receptor interaction pathways) are also significantly associated with COVID-19 and IPF diseases 69,[84][85][86][87][88][89][90][91] .…”
Section: Discussionmentioning
confidence: 71%